Will AI Enable Disease Eradication? A Critical Look at the Digital Frontier of Global Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Will AI Enable Disease Eradication? A Critical Look at the Digital Frontier of Global Health The goal of disease eradication—the permanent reduction to ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine